The use of Dynamic Panel Data to Estimate the Profitability of Conventional Banks - Widodo, Purwanto (Borong Newinera Publisher, 2026)
This study aims to analyze internal and macroeconomic factors that affect the profitability of conventional banks in Indonesia, using Return on Assets (ROA) and Net Interest Margin (NIM) proxy. Previous research has often ignored the issue of endogeny and persistence of profitability. Using dynamic panel data from 37 conventional banks during the period 2012–2024, this study applied the Two-Step System Generalized Method of Moments (GMM) method. The results confirm the existence of significant persistence of profitability. It was found that independent factors had different (divergent) impacts on ROA and NIM. Specifically: The Loan-to-Deposit Ratio (LDR) has a positive impact on ROA but negative on NIM. Non-Performing Loans (NPLs) have a negative impact on ROA, but surprisingly positive on NIM. Macro factors (GDP, Inflation, Interest Rates) also show a complex duality of impacts. Banks are advised to maintain optimal LDRs while increasing low-cost Third-Party Funds (DPK) and diversifying non-interest income. Regulators are encouraged to analyze NIM as the core of intermediation efficiency, not just ROA.